2021
DOI: 10.3390/ani11102971
|View full text |Cite
|
Sign up to set email alerts
|

Classic and Non-Classic Effects of the Duration of Supplementation of 25-Hydroxicholecalciferol in Broiler Chicken Diets

Abstract: The present study aimed to determine the effect of different times of supplementation of 25-hydroxycholecalciferol (25(OH)D3) in broiler chickens on the performance, carcass and cuts yield, bone resistance, plasma concentration of 25(OH)D3, and expression of the mTOR gene. The treatments were a control diet (CD) supplemented with 3000 IU vitamin D3/kg of feed from 1 to 46 d, or the CD + 2760 IU (69 mcg) of 25(OH)D3/kg of feed from 1 to 21 d, from 1 to 35 d, or from 1 to 46 d. The period of supplementation of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies conducted in humans have shown that there is a correlation between low vitamin D status and increased body fat percentages [33,34]. Furthermore, it was shown in fattening broiler chicks that a supplementation with 25-OHD 3 accompanied by higher plasma concentrations of 25-OHD 3 stimulates breast muscle development and increases protein deposition, probably via the mTOR pathway [35,36]. In the present study, dietary supplementation with 25-OHD 3 had no effect on daily feed intake in lactation and the change in body weight during gestation and lactation.…”
Section: Body Condition and Compositionmentioning
confidence: 99%
“…Studies conducted in humans have shown that there is a correlation between low vitamin D status and increased body fat percentages [33,34]. Furthermore, it was shown in fattening broiler chicks that a supplementation with 25-OHD 3 accompanied by higher plasma concentrations of 25-OHD 3 stimulates breast muscle development and increases protein deposition, probably via the mTOR pathway [35,36]. In the present study, dietary supplementation with 25-OHD 3 had no effect on daily feed intake in lactation and the change in body weight during gestation and lactation.…”
Section: Body Condition and Compositionmentioning
confidence: 99%